STUDENTS LEARNING MOTIVATION IN AQIDAH AND AKHLAK: AN EXPERIMENTAL STUDY OF THE SNOWBALL THROWING MODEL ASSISTED BY GIMKIT MEDIA - Nur Hikmah; Siti Zulaikhah; Baharudin Baharudin (Program Studi Pendidikan Agama Islam, 2026)
The purpose of this study is to examine how well the cooperative learning model, which uses the Snowball Throwing technique and is supplemented by Gimkit media, can increase the learning motivation of eleventh-grade students at MAN 2 Bandar Lampung in the Akidah Akhlak topic. The study used a posttest-only control group design using a quantitative, quasi-experimental methodology. Two classes were chosen by simple random sampling to make up the research sample: a control class that was taught using traditional teaching techniques and an experimental class that received instruction using the Snowball Throwing model with assistance from Gimkit. A learning motivation questionnaire was used as the study tool; its validity and reliability were assessed using Cronbach's Alpha, which produced a coefficient of 0.750. Normality and homogeneity tests were used to analyze the data, and then an independent samples t-test was performed. The results indicated that the data were normally distributed and homogeneous. The results of the t-test analysis showed a statistically significant difference in learning motivation between the experimental and control groups, with a significance value of 0.000 (p < 0.05). Thus, it has been demonstrated that the Snowball Throwing learning approach, which Gimkit supports, improves students' motivation to learn in the Akidah Akhlak course. The integration of the Snowball Throwing cooperative learning model with a gamification-based digital medium, specifically used in Akidah Akhlak instruction at the Madrasah Aliyah level, is what makes this study novel.